Impact of benefit sanctions on unemployment outflow: Evidence from German survey data - Katja Hillmann; Ingrid Hohenleitner (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
Similar to numerous other European countries, Germany's unemployment policy went through a paradigm shift towards activation policy by tightening their monitoring and sanction regime. In our study we examine the impact of benefit sanctions on the probability of getting employed or leaving the labor force. Using a mixed proportional hazard model, we draw causal inference of sanction enforcements on unemployment exit hazards. Based on a novel survey sample, covering the first three years after implementation of the Hartz IV law in 2005, we provide evidence for a positive impact of sanctions on employment entrance, but also on leaving the labor market.
Keywords: J48; J63; J64; J68; I38; 330; unemployment benefit sanctions; unemployment duration; employment; non-employment; mixed proportional hazard estimation; Hartz-Reform; Arbeitslosenversicherung; Sozialhilfe; Strafe; Aktivierende Sozialhilfe; Wirkungsanalyse; Arbeitslosigkeit; Deutschland